Differences in microbial communities between healthy and bleached coral Acropora solitaryensis from Xisha Islands, South China Sea. Issue 10 (25th November 2016) - Liu, Zhuhong; Chen, Chang; Gao, Lei; Zhang, Yuyang; Pei, Jingjing; Ren, Chunhua; Hu, Chaoqun
ABSTRACT: Serious bleaching events have been observed in Acropora solitaryensis, one of the main species of reef-building coral in the area of the Xisha islands in the South China Sea, during 2008–2011. The microbial communities of healthy and bleached coral samples were compared to explore the difference in the bacterial composition using 16S rRNA gene sequencing and denaturing gradient gel electrophoresis (DGGE). Analysis of 16S rRNA gene sequences showed that the diversity of bacteria from the corals was different between the healthy and the bleached. Albeit both the healthy coral and bleached coral displayed similar dominant bacterial species (α- and γ-proteobacteria), the ratio of Vibrio spp. increased sharply in the latter. As the bleaching developed, the diversity of the microbial community was dramatically decreased and the dominant species were replaced by γ-proteobacteria where Vibrio spp. and Escherichia spp. overwhelmed other genera. Similar results were gained by the DGGE technique though the abundance was lower. Furthermore, in the bleached tissues, Vibrio coralliilyticus was identified using both methods. These results indicated that pathogenic Vibrio spp. might be one of the factors causing A. solitaryensis bleaching in the coral reef of the Xisha islands.